Design of Hybrid Model of Fertilizers Production Process for Automatic Control Purpose - Oberauskas, G.; Galvanauskas, V. (Elektronika ir Elektrotechnika, 2011)
An improved technique of hybrid modeling of fertilizers production processes for automatic control purpose is described. Design principles of mass balance systems for key components are outlined, and artificial neuron network (ANN) subsystems for modelling of absolute reaction rates are represented for ammonia production processes. The sensitivity equation approach was applied for parameters identification of a hybrid model for ammonia production processes. Possible difficulties and ways of practical implementation of the applied identification method for complex hybrid models for industrial chemical processes are outlined. The hybrid model identification results are presented and discussed. Ill. 5, bibl. 6 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.114.8.704